Pth-carrying high-strength hydrogel promotes bone defect reconstruction via the PTH1R/SLPI pathway - Gang Xiang; Feng Zhong; Yi Yin; Linhua Deng; Ang Deng; Yunjia Wang; Zejiu Tan (Materials & Design)
The repair of bone defects, particularly those of a substantial size, has historically posed considerable challenges due to insufficient blood supply and the absence of attachment points. Hydrogels have seen a surge in applications in wound healing and drug delivery due to their exceptional biocompatibility and biodegradability. In this study, a high-strength hydrogel (G/mA Gel) was developed to promote bone defect repair by loading parathyroid hormone (PTH). The PTH-G/mA Gel demonstrated the capacity to release PTH in a continuous and stable manner, thereby significantly enhancing the differentiation of MC3T3 osteoblasts. In a rat skull defect model, the bone density and bone volume of the PTH-G/mA gel group were significantly higher than those of the control group and the group using PTH alone. Subsequent analysis revealed that this enhancement was attributable to the slow-release mechanism of PTH, which exerted a synergistic effect on osteogenesis by activating the PTH1R/SLPI pathway in conjunction with the mechanical reinforcement provided by the hydrogel at the defect site. This study proposes a novel, cost-effective strategy with minimal adverse effects, providing a new avenue for the treatment of bone defects.